Islamic Business Ethics in Entrepreneurship in Promoting MSME Actors - Nadia Ulfa; Zuhrinal M. Nawawi (Penerbit Jurnal Indonesia, 2022)
In doing business for SMEs, Islamic business ethics has a major impact on their business. Therefore, the purpose of this study is how Islamic business ethics can advance and improve the business of MSME actors. In conducting this research, the researcher uses a qualitative descriptive method, where the data obtained through the analysis of previous research and also uses accurate reading reference sources such as journals, books, articles, and trusted websites. As for the results, the results obtained are that MSME actors are fully aware that Islamic business ethics has a major influence on their business, seen from MSME actors who have widely applied Islamic business ethics in production, consumption and distribution. Because MSME actors strongly believe that Islamic business ethics can advance their business so that they experience a significant increase.